152k views
0 votes
20 points.
Please answer and explain if possible.
Multiply.
-2y^2 * xy^4

User Vasart
by
4.9k points

2 Answers

6 votes

Answer:


\large\boxed{-2xy^6}

Explanation:


-2y^2\cdot xy^4=(-2)(x)(y^2y^4)\\\\\text{use}\ a^na^m=a^(n+m)\\\\=-2xy^(2+4)=-2xy^6

User Peter Mitrano
by
4.9k points
2 votes

When the bases are the same, you can combine the exponents.

x³ [x is where the base is]

For example:

x³ · y² = x³y² You can't simplify this anymore because they have different bases/variables

[when you multiply a variable with an exponent by a variable with an exponent, you add the exponents together] so:

x² · x³ =
x^(2+3)=x^5

[when you multiply a variable with an exponent by an exponent, you multiply the exponents together] so:

(x³)²=
x^(3*2)=x^6


-2y^2*xy^4=-2x(y^(2+4))=-2xy^6

User Derekantrican
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.